(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2014)
Background: Promoting sexual and reproductive health of adolescents contributes to their personal and social education (Ramiro et al, 2011). However, there is often a gap between the perception of the school about the sexuality of their students and the reality they actually live in. As so, the SE projects implemented may not coincide with the young people real needs (Allen, 2008). Objectives: This research aims to identify the needs of basic education students on human sexuality and sex education (SE) and, from these, to develop their skills in order to promote a healthy sexuality. Participants: We worked with a convenience sample of 2nd and 3rd cycle students of Portuguese basic education attending a school in urban milieu. Methods: Being an action-research project, at the diagnostic phase we carried out a questionnaire for the second and the third cycle of basic education students attending an Oporto school. Questionnaire was filled in online by 397 students. The data obtained were taken into account when developing a SE program applied to 6th, 7th, 8th and 9th grade students, in the school by teachers. After the program we applied a new questionnaire, which was filled in on paper by 112 students, in order to ascertain the changes occurred. Results: About 47% of the students acquired a comprehensive concept of sexuality, against the 43,1% that in the diagnostic phase only considered the biologic dimension of sexuality. The intervention group of students revealed more knowledge about reproduction, sexually transmitted infections, contraception, pregnancy and hygiene. Students who participated in SE activities agreed more than those in the diagnose phase that school is a place where they could clarify doubts about sexuality and that teachers were able to clarify them. These students also agreed more that they wanted to participate in more SE activities. Conclusions: A SE intervention that considers the needs of their target audience has a greater probability of effectiveness.